The Role of Microfinance Institutions in Community Economic Empowerment: Perspectives of Actors and Customers - Putri, Siti Rahmayanti; Aldine, Thia Thania; Darus, M. Aza Raja; Aulia, Dinda; Hayati, Fitri (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Microfinance institutions (MFIs) play an important role in community economic empowerment, especially for micro, small, and medium enterprises (MSMEs) and low-income groups that are not covered by formal financial institutions. This study uses the literature review method to analyse the strategic role of MFIs in supporting community economic improvement from the perspective of the actors and clients. The results of the study show that MFIs not only provide financial services, but also act as initiators, facilitators, and assistants in the empowerment process. MFIs support business development through the provision of capital, financial education, and management training, which helps MSMEs improve business quality and competitiveness in the market. In addition, MFIs contribute to creating financial inclusion in remote areas and support the empowerment of women in entrepreneurship. The multiplier effect of optimising the role of MFIs includes increasing community income, reducing poverty, creating new jobs, and strengthening the national economy in a sustainable manner. Therefore, institutional strengthening, human resource capacity building, and synergy between the government and MFIs are needed to support more equitable and sustainable community economic empowerment.